Are graphene and graphene-derived products capable of preventing COVID- 19 infection? (2020)
The Severe Acute Respiratory Syndrome CoronaVirus 2 (SARS-CoV-2) causes the new coronavirus disease 2019 (COVID-19). This disease is a severe respiratory tract infection that spreading rapidly around the world. In this pandemic situation, the researchers' effort is to understand the targets of the virus, mechanism of their cause, and transmission from animal to human and vice-versa. Therefore, to support COVID-19 research and development, we have proposed approaches based on graphene and graphene-derived nanomaterials against COVID-19.